3D printing of carbon black/polypropylene composites with excellent microwave absorption performance. (10th November 2020) - Lei, Lei; Yao, Zhengjun; Zhou, Jintang; Wei, Bo; Fan, Huiyuan
Abstract: 3D printing in virtue of strong designability has incomparable advantages in material composition and structural design. In this work, carbon black/polypropylene composite with various contents of carbon black (CB) were successfully prepared by fused deposition modeling. When the CB content is 10%, uniformly dispersion of particles in the matrix with little agglomeration, and the corresponding composite exhibits the excellent microwave absorption and broad effective bandwidth. The maximum reflection loss value reached −39.15 dB at 15.08 GHz, and the corresponding effective bandwidth is 5.63 GHz (12.37–18 GHz) with a thickness of 2.1 mm. At the same time, when the thickness is 2.8 mm, the maximum reflection value is up to −62.6 dB at 10.64 GHz with an effective bandwidth of 4.56 GHz (8.88–13.44 GHz). The composite containing 10 wt% CB has conductive loss, polarization loss, and suitable impedance matching, resulting in superior microwave absorption. 3D printing technology provides a more efficient method for the preparation of microwave absorbing materials. Graphical abstract: Image 1